Signet ring cell carcinoma of the gastrointestinal tract: National trends on treatment effects and prognostic outcomes. (2021) - Franko, Jan; Le, Viet H.; Tee, May C.; Lin, Mayin; Sedinkin, Jessica; Raman, Shankar; Frankova, Daniela
Highlights: In this cohort study based on 913, 059 gastrointestinal carcinomas reported to the United States national cancer Database, the signet ring cell carcinoma diagnosis was associated with significantly worsened overall survival (adjusted HR = 1.37). The magnitude of survival disadvantage was site-dependent, and most evident for rectal signet ring cell carcinomas (adjusted HR = 2.37). Both systemic therapies and resection were associated with benefit across examined histologies and primary sites. Abstract: Background: Signet ring cell carcinoma (SRCC) is a distinct malignancy occurring across the tubular gastrointestinal tract (tGIT). We comprehensively examined the outcomes of patients diagnosed with SRCC across tGIT. Methods: SRCC and not-otherwise-specified adenocarcinoma (NOS) patients reported to the National Cancer Database from 2004 to 2015 were included. Baseline characteristics, outcomes and site-specific adjusted hazard ratios (aHR) derived from Cox models of SRCC patients were compared to those of NOS patients. Overall survival (OS) was primary endpoint. Results: A total of 41, 686 SRCC (4.6%) and 871, 373 NOS patients (95.4%) were included. SRCC patients were younger (63.1 ± 14.7 vs. 67.0 ± 13.4 y, p < 0.001) and more likely to present with Stage IV disease than NOS patients (42.5% vs. 24.5%, p < 0.001). Stomach ( n = 24, 433) and colon ( n = 9, 914) contributed highest frequency of SRCC. SRCC histology was associated with shorter OS (aHR = 1.377, p < 0.001) in multivariate model. There was an interaction between SRCC and chemotherapy effects on risk of death (interaction aHR = 1.072, pinteraction < 0.001) and between SRCC histology and disease site, suggesting that the effect of SRCC on OS is site-dependent, with a higher increased risk of death in patients with rectal SRCC (aHR = 2.378, pinteraction < 0.001). Conclusion: Significant negative prognostic effect associated with SRCC is site-dependent across the GIT. Surgical and or systemic therapy was associated with improved OS among SRCC patients, but remained lower than NOS patients. Further understanding of gastrointestinal SRCC molecular profile is needed to better inform future treatment strategies.